The Mexican Political System in Transition: The End of an Era - Negrete Mata, José (Frontera Norte, 2017)
San Diego, La Jolla, Center for U.S. Mexican Studies de la Universidad de California en San Diego, 1991. Wayne A. Cornelius y Ann L. Craig